A Kid's Guide to How Plants Grow - Ayers, Patricia (New York : Rosen Pub. Group's PowerKids Press, 1999)
This book briefly describes how different kinds of plants grow and reproduce, as well as their importance to life on Earth.
Includes index.
Includes glossary.
K-3
AR Accelerated Reader
Keywords: Indoor gardening; House plants